Evaluasi Pelayanan Kinerja Angkutan Pemadu Moda di Bandara Soekarno Hatta dan Upaya Peningkatannya - Rita, Rita; Sinaga, Rosita (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Soekarno-Hatta International Airport as a gateway has supported facilities such as the availability of airport transportation service integrator modes, namely: Damri Bus, Taxi, Bus Primajasa, Cipaganti Shuttle, Shuttle Bus, Transport Charter, City transport, and Motor Vehicle/Ojek as an alternative option for passenger air transport to final destination in Soeakrno Hatta Airport. Based SKEP. Adbandara Number ADSH.03/HK.30/III/2000, concerning Rules and Procedures of activities at Soekarno Hatta Airport in Article 78 regarding the operation of public transportation (1) describedthe permission of the operation of public transport in Soekarno Hatta Airport by the Directorate General of Land Transportation. Airline flight schedules both domestic and international flights have been adapted to the schedule of available modes of transport integrator at Soekarno Hatta Airport for passengers who want to use a transportation mode integrator who will travel tmuards the final destination is not too long to wait in the waiting room Soekarno Hatta Airport.Keywords: Service, Performance Feeder Transportation